Novel Digital Measurement Technique to Analyze the Palatine Suture Expansion after Palatine Rapid Maxillary Expansion Technique - Requena Pérez, Mariano; Zubizarreta Macho, Álvaro; Colino Gallardo, Pedro; Albaladejo Martínez, Alberto; Garcovich, Daniele; Alvarado Lorenzo, Alfonso (My University, 2021)
The aim of the study was to validate a novel digital measurement method to quantify the volume of the midpalatal suture after rapid maxillary expansion (RME). Material and methods: Eight patients with maxillary skeletal transverse deficiency were submitted to palatine suture expansion using the McNamara orthodontic appliance during a period of nine months. After 30 days of treatment, all patients were exposed postoperatively to a cone-beam computed tomography (CBCT) scan. Afterwards, the scans were uploaded into the three-dimensional orthodontic-planning software to allow the volumetric assessment of the palatine suture expansion through palatine rapid maxillary expansion using a McNamara appliance. The repeatability was analyzed by repeating twice the measures by a single operator and reproducibility was analyzed by repeating three times the measures by two operators, and Gage R&R statistical analysis was performed. Results: The expansion of the midpalatal suture by means of the rapid maxillary expansion technique, in terms of digital volume measurement, showed a repeatability value of 0.09% and between the two operators a reproducibility value of 0.00% was shown. Conclusions: The novel measurement technique demonstrated a high repeatability and reproducibility rate for volume assessment of the palatine suture expansion through palatine rapid maxillary expansion technique.
Keywords: orthodontics; palatine suture expansion; rapid maxillary expansion; digital dentistry; McNamara appliance